2023
DOI: 10.3390/pharmaceutics15051346
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for the Use of Metal-Based Nanoparticles as Adjuvants for Local Cancer Immunotherapy

Abstract: Immunotherapy is among the most effective approaches for treating cancer. One of the key aspects for successful immunotherapy is to achieve a strong and stable antitumor immune response. Modern immune checkpoint therapy demonstrates that cancer can be defeated. However, it also points out the weaknesses of immunotherapy, as not all tumors respond to therapy and the co-administration of different immunomodulators may be severely limited due to their systemic toxicity. Nevertheless, there is an established way t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 257 publications
0
2
0
Order By: Relevance
“…Moreover, AuNPs can promote the function of T lymphocytes and enhance antitumor immunity by cross-presenting antigens [ 220 ]. These remarkable characteristics position AuNPs as good candidates for cancer vaccine treatments [ 215 , 218 , 221 , 222 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, AuNPs can promote the function of T lymphocytes and enhance antitumor immunity by cross-presenting antigens [ 220 ]. These remarkable characteristics position AuNPs as good candidates for cancer vaccine treatments [ 215 , 218 , 221 , 222 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that metal nanoparticles are capable of preventing sudden drug release and avoiding off-target effects, which gives it many advantages such as improved pharmacokinetic properties and flexible control of drug release ( 13 , 14 ). Moreover, several studies have shown that metal nanoparticles, modulated by surface ligands or intrinsic properties, can respond to the unique chemical properties of TME by precisely delivering immunomodulatory factors to target tissues or specific immune cells, to achieve an effective and enhanced immune response for enhanced therapeutic efficacy ( 15 17 ). Recently, there are a large number of metal nanoparticles have been developed, such as gold, silver, copper, bismuth, manganese, iron, platinum and lead, which can be applied in various modalities of cancer therapy in different forms such as antibodies, solids and coatings ( 18 21 ).…”
Section: Introductionmentioning
confidence: 99%